2016
DOI: 10.1038/ncomms11081
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity controls Bdnf expression via Polycomb de-repression and CREB/CBP/JMJD3 activation in mature neurons

Abstract: It has been recently described that in embryonic stem cells, the expression of some important developmentally regulated genes is repressed, but poised for fast activation under the appropriate stimuli. In this work we show that Bdnf promoters are repressed by Polycomb Complex 2 in mature hippocampal neurons, and basal expression is guaranteed by the coexistence with activating histone marks. Neuronal stimulation triggered by N-methyl-D-aspartate application induces the transcription of these promoters by H3K27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 66 publications
6
78
0
Order By: Relevance
“…Our observations are consistent with other work demonstrating that EZH2 partially inhibits SLIT2 expression in a variety of cancers and that SLIT2 expression can be increased by interfering with EZH2 function (Yu et al, 2010). Furthermore in hippocampal neurons, it has been shown that neuronal stimulation can de-repress Bdnf expression by displacement of Ezh2 from the Bdnf promoters (Palomer et al, 2016) and that Ezh2 knockdown can de-repress Runx2/p57 (Aguilar et al, 2016). Knockdown of specific lncRNAs, even in fully differentiated cells, has been shown to displace PRC2 thus de-repressing gene transcription (Gonzalez et al, 2015; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are consistent with other work demonstrating that EZH2 partially inhibits SLIT2 expression in a variety of cancers and that SLIT2 expression can be increased by interfering with EZH2 function (Yu et al, 2010). Furthermore in hippocampal neurons, it has been shown that neuronal stimulation can de-repress Bdnf expression by displacement of Ezh2 from the Bdnf promoters (Palomer et al, 2016) and that Ezh2 knockdown can de-repress Runx2/p57 (Aguilar et al, 2016). Knockdown of specific lncRNAs, even in fully differentiated cells, has been shown to displace PRC2 thus de-repressing gene transcription (Gonzalez et al, 2015; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The decline of H3K27me3 may result in the dissociation of EZH2. It has been reported that upon NMDA stimulation, H3K4me3 at the Bdnf promoter increased and serine 28 of H3K27me3 was phosphorylated by p38-mitogen-activated protein kinase (MAPK)/mitogen- and stress-activated protein kinase 1 and 2(Msk1/2), which in turn replaced EZH2 [35]. Simultaneously, Bdnf expression increased (RNA-seq) (Figure 2F).…”
Section: Histone Modifications Around Mouse Bdnfmentioning
confidence: 91%
“…Furthermore, different stimuli induce Bdnf transcripts. Kainic acid, a glutamate analogue, induced transcription of Bdnf exons I, IV, V VII, VIII and IXA in rat hippocampus while N -methyl- d -aspartate (NMDA) treatment identified Bdnf exons II and IV, but not I and III, as fast-reacting exons [15,35]. These data suggest that stimulations might affect histone modifications at different promoters, resulting in different transcripts of exons in distinct brain regions.…”
Section: Histone Modifications Around Mouse Bdnfmentioning
confidence: 99%
“…The activity of H3K27me3 specific demethylases is regulated by intracellular levels of α-ketoglutarate that fluctuate in response to neuronal activation [105]. Additionally, neuronal activation can directly phosphorylate histone H3 at Ser28 (H3S28p), leading to the displacement of PRC2 [106].…”
Section: Polycomb Group Complexes In Mature Neurons and Neurodegeneramentioning
confidence: 99%